New onset atrial fibrillation after percutaneous Patent Foramen Ovale closure: how serious is this problem?. (25th November 2020) - Ferreira, V; Almeida Morais, L; Sousa, L; Fiarresga, A; Martins, J.D; Timoteo, A.T; Viveiros Monteiro, A; Loureiro, P; Soares, C; Castelo, A; Garcia Bras, P; Reis, J; et al.
Abstract: Background: Percutaneous Patent Foramen Ovale (pPFO) closure benefits for secondary prevention after cardio-embolic stroke have recently been proved. With the increasing number of cases and procedures, a concern with new onset atrial fibrillation (NOAF) has been raised. Purpose: To evaluate long-term outcome regarding NOAF rate and to identify its predictors and clinical impact, in a real population submitted to pPFO closure. Methods: From 2000 to 2017, consecutive patients (P) submitted to pPFO closure in a tertiary centre were prospectively enrolled. The primary endpoint was NOAF rate and secondary endpoints were all-cause, neurologic and cardiac mortality rates and recurrent ischemic events. Previous and follow-up electrocardiographic, echocardiographic and 24-hour heart rhythm monitoring data were analysed. Follow-up was performed through medical visits, medical charts consultation and a phone call based system, in order to assess clinical status, on-going treatment and events. Results: 496 patients were submitted to pPFO. Immediate success was achieved in 98.8% and 9.1% presented a residual shunt on the 1st year TEE. Mean age was 45.0±11.2 years-old with 50.2% of males. The prevalence of hypertension, hypercholesterolemia and atrial septum aneurysm (ASA) was 25.7%, 45.0% and 46.3%, respectively. Pre-procedural mean left atrial (LA) diameter was 36.0±5.3 mm. FU data was available for 490 (98.6%), for a mean FU time of 7.41±3.51 years. 34 P (6.9%) presented ischemic events recurrence (26 strokes and 8 TIA). The primary endpoint was observed in 21 P (4.3%) during the FU period. Median time to 1st AF episode since PFO closure was 5.90±5.53 years. 11 P (52.3%) initiated oral anticoagulation. In univariate analysis, age (44.6±11.3 vs 51.8±6.0 years, p=0.005) and hypertension (24.7% vs 47.6%, p=0.019) were predictors of NOAF in this population. In multivariated analysis, only age remained a predictor of NOAF (OR 1.05 (1.007–1.101), p=0.025). LA pre pPFO closure dimensions, ASA, device type or size and the presence of residual shunt in TEE were not determinants of AF occurrence. The incidence of NOAF was associated with the need for hospitalization due to cardiac causes (19% vs 3.2%, p=0.001) and a trend towards higher rate of recurrent stroke (4.9% vs 14.3%, p=0.06). Conclusion: Despite being a highly successful and safe procedure in most patients, pPFO closure was associated with a non-negligenciable rate of NOAF during long-term follow-up. NOAF predictors were related with classical cardiovascular risk factors, such as age and hypertension. None of the procedure or device features were associated with NOAF. Yet, a clinical impact was attributed to NOAF, with more hospitalizations and a trend towards ischemic events recurrence. As young patients submitted to pPFO closure grow older, prevention strategies to diagnose and treat NOAF should be endeavoured. Funding Acknowledgement: Type of funding source: None